Cymatics Soundscapes: And Bringing Matter to Life with Sound - Jenny, Hans (Eliot Macromedia, 2006)
If youre someone who is interested in the healing powers of sound and vibration, I think youll have the same kind of epiphany as I had when I met Dr. Manners in 1977 in London. I was introduced to dramatic visual proof that sound has demonstrable effects on solids, liquids and gases, and have featured them in my workshops ever since.If you want to deepen your understanding and appreciation of our world, you must see, and hopefully own, the new Cymatics Soundscapes DVD.Those of you familiar with the film What the Bleep Do We Know!? may remember these photos, as well as those of Dr. Masaru Emoto and frozen water crystals. Cymatherapy® is the name of a new branch of sound therapy. Their unique delivery system is comprised of a computer program and applicator that is placed on the surface of the skin. This non-invasive technology transmits special combinations of audible sound, using frequencies associated with healthy cells, to support the bodys natural healing abilities.